한국의 표고 톱밥재배 품종의 에르고티오네인 함량 분석 - 김민준; Min-jun Kim; 정연석; Yeun Sug Jeong; 김은진; Eunjin Kim; 장영선; Yeongseon Jang; 가강현; Kang-hyeon Ka (Hangug gynnhaghoi ji, 2022)
Lentinula edodes is a type of mushroom widely consumed in East Asia, and many of the components contained in them are used as raw materials for pharmaceuticals or as health supplements. Ergothioneine, a sulfur-containing amino acid in L. edodes, is attracting attention due to its antioxidant and anti-inflammatory effects. L. edodes generally contain an ergothioneine content of about 200 to 800 mg per kg; there are some differences in this value depending on the cultivation conditions. In this study, 24 domestic sawdust-cultivated L. edodes cultivars were cultured under the same conditions, and the morphological characteristics and ergothioneine content of the fruiting bodies were investigated. The yield and morphological characteristics of the fruiting bodies were different in each cultivar. Taehyanggo and Sanjo 713ho had the largest and thickest pileus. The pileus of L. edodes had a higher ergothioneine content than the stipe. Sanjo 715ho had the highest ergothioneine content in the pileus and the stipe at 1,225 mg/kg and 753 mg/kg, respectively. An ergothioneine content of more than 1,000 mg/kg in the pileus was observed in Bambithyang, Sansanhyang, Sulbaekhyang, Taehyanggo, Sanjo 705ho, Sanjo 709ho, Sanjo 715ho, and Sanjo 716ho. These cultivars can be used as parental strains to develop new cultivars with enhanced ergothioneine functionalities.